Placement of Regional Apparatus Based on Merit in Structural Position Based on System Thinking Approach - Qomariyah, Erni; Zauhar, Soesilo; Muluk, Mujibur Rahman Khairul; Setyowati, Endah (FIA UB, 2018)
Placement of structural officials in the Momahe City administration still holds the problem. The problem occurs because there is a different legal basis used in the placement of structural officials. For appointment of echelon II / b officials using PAN-RB Regulation no. 13/2014 on openly charging the Office of the Leader. As for the placement of Echelon III and IV still use Government Regulation no. 100/2000. In this last rule the role of the Agency for the consideration of position and rank is very dominant. This dominance led to the imposition of Echelon II structural officials under the prone to bureaucratic politicization. Novelty of this research is to see the reality of the problem of placement of structural positions by looking at the relationship between the elements with each other with systems thinking approach. This study aims to create a model of organizing the placement of structural positions in the city government Momahe. The results showed that systemically the placement of structural officials based on merit showed two behaviors, namely reinforcing and balancing.